NMR spectroscopy in pharmaceutical analysis - Holzgrabe, U. (Ulrike); Wawer, I. (Iwona); Diehl, B. (Bernd); ScienceDirect eBooks (Oxford : Elsevier, 2008)
For almost a decade, quantitative NMR spectroscopy (qNMR) has been established as valuable tool in drug analysis. In all disciplines, i. e. drug identification, impurity profiling and assay, qNMR can be utilized. Separation techniques such as high performance liquid chromatography, gas chromatography, super fluid chromatography and capillary electrophoresis techniques, govern the purity evaluation of drugs. However, these techniques are not always able to solve the analytical problems often resulting in insufficient methods. Nevertheless such methods find their way into international pharmacopoeias. Thus, the aim of the book is to describe the possibilities of qNMR in pharmaceutical analysis. Beside the introduction to the physical fundamentals and techniques the principles of the application in drug analysis are described: quality evaluation of drugs, polymer characterization, natural products and corresponding reference compounds, metabolism, and solid phase NMR spectroscopy for the characterization drug substances, e.g. the water content, polymorphism, and drug formulations, e.g. tablets, powders. This part is accompanied by more special chapters dealing with representative examples. They give more detailed information by means of concrete examples. . combines theory, techniques, and concrete applications-all of which closely resemble the laboratory experience . considers international pharmacopoeias, addressing the concern for licensing . features the work of academics and researchers, appealing to a broad readership.
Part I: Fundamentals and Techniques. 1. NMR Spectroscopy in drug analysis; application in international pharmacopoieae and related analyses. (U. Holzgrabe, B. Waibel, C. Schollmayer). 2. Principles in NMR spectroscopy. (B. Diehl). 3. qNMR in solid state NMR. (I. Wawer). 4. qNMR. (F. Malz) 5. Internal standards for quantification and pattern recognition, e.g. ERETIC; and principal component analysis of mixtures, e.g. beverages (Amix & trade;). (M. Spraul, E. Humpfer). 6. Microcoil NMR spectroscopy/Nanoliter-Volume NMR spectroscopy. (A.G. Webb). Part II: General Applications 7. NMR spectroscopy in impurity profiling including aspects of pharmacopoeia. (U. Holzgrabe). 8. NMR spectroscopy of pharmaceutical polymers. (B. Diehl). 9. Natural Products analysis by qNMR. (B. Diehl). 10. Solid-state measurements of drugs and drug formulations. (I. Wawer) Part III Special Applications. 11. NMR assays for identity of polysaccharides from bacteria used in vaccine manufacture. (C. Jones, N. Ravenscroft). 12. Metabolic profiling. (C.K. Larive). 13. Fluorine-19 and phosphorus-31 NMR for quantitation of fluorinated and phosphorylated drugs and their metabolites in biofluids. (M. Malet-Martino). 14. Solid-state measurements of bones. (C. J̃ger). 15. qNMR for assessing the purity of agrochemicals (R.J. Wells). 16. Assessment of inhibitory potency of antibiotics by MRI (C. Faber). 17. Quantitation 2D NMR analysis of glycosaminoglycans. (G. Torri). 18. DOSY NMR for Drug Analysis. (M. Malet-Martino, et al). 19. NMR spectroscopy of peptides as an alternative to AAA. (E. Kellenbach, K. Sanders, P.L.A. Overbeeke). 20. The Hypernation of NMR and Other Spectroscopies in Drug and Natural Products Research. (I.D. Wilson). 21. Online-NMR-Spektroscopy. (H. Hasse).
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Nuclear magnetic resonance spectroscopy; Drugs -- Analysis; MEDICAL -- Drug Guides; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; MEDICAL -- Nursing -- Pharmacology; Drugs -- Analysis; Nuclear magnetic resonance spectroscopy; Electronic books